(untitled) (Eurasian Journal of Philology Science and Education, 2015)
The article deals with the main role of mass media information, which for a modern person images in reality of his personal interpretation. There fore, the informational model of world formation becomes the major direction in creating the image of the world by individual. The author underlines the attention for the main way of newspaper – published speech, as a value criteria, which forms necessary style formation function for newspaper discourse.